The state of indicators of the angio-OCT of the macular area in pregnant women with preeclampsia in conjunction with the content of the factor of endothelial dysfunction, their importance for predicting vascular retinal pathology in the postpartum period - O. V. Кolenko; E. L. Sorokin; N. S. Khodzhaev; G. V. Chizhova; A. A. Fil; N. V. Pomytkina; Ya. E. Pashentsev (Офтальмохирургия, 2019)
Purpose. Clinical assessment of the hemodynamic state of the macula in pregnant women with preeclampsia in conjunction with the content of endothelial dysfunction factors, their importance in predicting vascular retinal pathology in the postpartum period.Material and methods. The main group consisted of 46 pregnant women with preeclampsia (PE) from 19 to 40 years. 36 women had a moderate degree of PE, and 10 women had a severe degree. The 1st comparison group included 20 pregnant women with a physiological course of pregnancy, from 18 to 38 years. The 2nd comparison group included 16 non-pregnant women with occlusions of the branches of the central retinal vein (CRV), aged 34 to 45 years. The control group consisted of 20 healthy, non-pregnant women from 19 to 38 years. All patients underwent determination of the level of endothelin-1 (E) in the lacrimal fluid (LF), the state of hemodynamics of the macular area was investigated using optical coherent tomography with angiography function (angio-OCT).Results. The highest values of the average level of E in LF occurred in the main group and in the 2nd comparison group (2.5±1.1 and 2.6±0.4 ng / ml, respectively). In the 1st comparison group in the 3rd trimester of pregnancy, the indicators of the total average density of the superficial vascular plexus in the macular region (DS), the density of the superficial vascular plexus in the fovea (DF), the density of the superficial vascular plexus in the parafova (DP), the area of the retinal avascular area (NFA) and subfoveal thickness of the choroid (CTX) had statistically significant differences from the control (p<0.01), but after 6–9 months after birth, these differences disappeared, although the difference in DS, DP values remained.Conclusion. In women with PE in the 3rd trimester of pregnancy, there was a statistically significant increase in E level in the LF and the deterioration of the angio-OCT of the macular ar ea.